A local review of section 17 leave forms in conjunction with the Mental Health Act Code of Practice: recommendations for future practice - Shayanthan Pathmanathan; Georgina Edgerley Harris; Giles Townsend (BJPsych Bulletin)
Aims and method The aim of this project was to set out recommendations for the section 17 leave form to reflect guidance provided in the Mental Health Act 1983: Code of Practice, following local Care Quality Commission feedback. We reviewed guidance in the Code and publicly available leave forms to identify items to include in the leave form. Then, we determined which publicly available leave forms included each item and reviewed whether the item should be included in the leave form and whether any reformulation was needed.